POLA KOMUNIKASI PENDIDIK DALAM BERKOMUNIKASI TERHADAP ANAK AUTIS DISEKOLAH LUAR BIASA SEHATI KARIMUN - Eka Lenggang Dianasari; Rini Hernyta; Muhiri (Universitas Karimun Prodi S1 Pendidikan Luar Biasa, 2021)
This research aim to to know Pattern Communications Educator In Communicating To Child of Autis Extraordinary School is Liver of Karimun. Knowing factors any kind of resistor and supporter of Pattern Communications Educator In Communicating To Child of Autis Extraordinary School is Liver of Karimun. Research which used in this research is research qualitative. Method Research qualitative yield descriptive data in the form of oral words and also written and my me able to perceive from accurate object. Approach qualitative centre liver at public principles which constitute materialization a meaning of social symptoms in society. Result of conclusion of this penilitian is Communications done by educator to child of autis still in the form of one way communications of researcher to subjek. child of Autis have earned to converse but in doing communications of verbal still less and need instruction, communications and tuition of is non verbal often seen only conducting touch, body movement, and face expression.